COMPETITIVE INFLUENCE OF TNCS ON THE DEVELOPMENT OF NATIONAL ECONOMIES IN GLOBAL CONDITIONS - Halaziuk , N.M. (The actual problems of regional economy development, 2022)
At the present stage of development of the world economy - the stage of globalization, a significant role is played by transnational corporations, which become leading trading companies, investors, distributors of modern technologies, scientific and technological progress, stimulators of international labor migration. It was multinational corporations that laid the foundation for interdependent economic activity around the world, and later became the foundation of the global economy. Today, multinational corporations are not only the main actors in the world, but also an important part of the national economy, whose role is growing every year. In the context of the rapid development of globalization processes in the world economic space, an important trend is the development of TNCs. It is obvious that in today's conditions TNCs allow them to accumulate financial and investment flows in host and home countries, create incentives for innovative technologies and new products, introduce new methods and principles of effective management and promote competitiveness of the national economy. The purpose of this work is to study the competitive influence of TNCs on the development of national economies, the prospects of their activities in the growing globalization of world economic relations. In the process of research general and specific economic methods were used, namely abstract, logical, method of combining historical and logical, analysis and synthesis, calculation of absolute and relative values. Research has shown that TNCs are the largest players in the world economy, the efficiency of the national economy, its participation in WFP, the level of integration and international competitiveness depend more on the success of TNCs based in the country. The scientific novelty of the obtained results is that, the author proved, the key role of TNCs as the largest actor in the world economy, the level of integration and international competitiveness largely depend on the successful operation of TNCs. The practical significance of the results is that formulated and substantiated scientific findings, conclusions can be used to increase the international competitiveness of the national economy through the use of investment activities of TNCs in the deepening globalization.